Implementasi Kebijakan Online Single Submission pada Pelayanan Perizinan Usaha (Studi Kasus di DPMTSP Kota Bandung & Kabupaten Bandung) - Joni Dawud; Rodlial Ramdhan Tackbir Abubakar; Deni Fauzi Ramdani (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
Online Single Submission (OSS) is an application that can be used for all business registration and application processes as well as other licensing applications included in the business licensing service. This study aims to examine how the implementation of online single submissions on business licensing services in Bandung city and Bandung Regency. This study used descriptive qualitative approach, with observation, interview, and documentation as its data collection techniques. The research results showed that business licensing services using online single submissions are already good, but these efforts have not been running optimally, there are still obstacles that are often faced by DPMPTSP Bandung City and Bandung Regency, especially regarding supporting facilities and disharmony between central and regional regulations related to the implementation of online single submission.